From Flipped Classroom to Flipped Learning: Evolution of the Concept and Its Philosophical Foundations - I. I. Gnutova (Высшее образование в России, 2020)
Flipped learning is actually considered as one of the most discussed educational concepts. The Russian researchers mainly focus on the technology of the flipped learning method and analyze the recent practice of its application at all levels of national education system. The purpose of the present article is to explore the theoretical backgrounds of the flipped learning. based on groundwork literature on flipped learning and related concepts and using a descriptive method of study the paper explores the fundamental features of the flipped learning, outlines the main steps in the development of this educational technology and shows its evolution from the basic “flipped classroom” model to the modern “flipped learning” concept. Today we still can see a simplified understanding of the “flipped classroom” technology, which reduces it to a simple inversion of homework and classroom work. The paper shows that while using the inversion of homework and classroom work as the base principle, the flipped learning implies more conceptual changes in the learning process, namely, a radical rethinking of the role of the teacher, the student and the content of their face-to-face time. Flipped learning can be considered as a kind of educational meta-strategy that creates optimal conditions for the application of a personalized approach to learning, as well as of all the basic tactics of active learning. The relevance of the work is due to the need to adapt the learning process in higher education to the changes in the national education system, as well as to global socio-economic changes. The article contributes to the positive attitude to the current transformation process in national education, and provides Russian practitioners with a theoretical basis and explanation of some of the critical issues of flipped learning.